Implementación de protocolos de evaluación cualitativa de corrientes hidrológicas: Estudio de caso río Chiticuy, Duitama (2021)
This research aims to qualitatively determine the conditions of the Chiticuy river through the implementation of alternative protocols for the evaluation of water flows, and its possible replication by the community. For this purpose, the study area was characterized, physicochemical analyses were carried out and the visual evaluation protocol was applied along the river in a collaborative work with the community, and finally a geographic information system was developed for easy access and management. The results obtained by both evaluation methods, quantitative and qualitative, were consistent with each other, coinciding that there is a deterioration in the quality of the Chiticuy river as it enters the municipality of Duitama, and demonstrating the relevance of the protocol as an appropriate tool for continuous monitoring of water sources by the community